2007
DOI: 10.1111/j.1742-1241.2007.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of coronary microvascular function in women at risk for ischaemic heart disease

Abstract: The primary objective of the current review is to describe the assessment of coronary microvascular function by noninvasive imaging techniques in women at risk for and with ischaemic heart disease (IHD). The search criteria were the analyses of the related bibliography published in PUBMED database. Normal or minimal obstructive coronary artery disease (CAD) at angiography is a common finding in women with signs of ischaemia. Up to 50% of them will have coronary microvascular dysfunction, suggesting that the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…The design of a new and noninvasive test for the assessment of NOCAD is strongly desirable. Coronary endothelial dysfunction plays an important pathogenic role in NOCAD (7,11,12,27). The present study demonstrated that noninvasive digital assessment of peripheral endothelial function by RH-PAT significantly predicted IHD, particularly NOCAD.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The design of a new and noninvasive test for the assessment of NOCAD is strongly desirable. Coronary endothelial dysfunction plays an important pathogenic role in NOCAD (7,11,12,27). The present study demonstrated that noninvasive digital assessment of peripheral endothelial function by RH-PAT significantly predicted IHD, particularly NOCAD.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, regarding NOCAD, not only coronary spastic angina, but also microvascular spasm and microcirculatory insufficiency have been shown to be associated with coronary endothelial dysfunction (7,11,12), thus it could be possible to identify all these patients with IHD by physiological examination and evaluating endothelial dysfunction.…”
Section: See Page 1697mentioning
confidence: 99%
“…These conditions, whether alone or in conglomerate, lead to vascular endothelial injury and increased oxidative stress which further promote coronary atherogenesis [9]. Investigators have theorized that the higher prevalence of left ventricular hypertrophy and obesity in black women results in “microvascular angina” from decreased coronary vascular reserve [68].…”
Section: Risk Factors For Ischemic Heart Diseasementioning
confidence: 99%
“…The validity of angiography compared to the other methods in women having ischemic signs has been debated. With positron emission tomography (PET) it is possible to measure coronary microvascular functions, and Campisi [24] has observed up to 50% of women with ischemic signs to have dysfunction in coronary microcirculation even though they did not have stenotic coronary arteries according to angiography. In addition, cardiac syndrome X has been suggested to have pathophysiological mechanisms in the endothelial function of coronary microcirculation [25,26].…”
Section: Discussionmentioning
confidence: 99%